Real-Time Determination of Photosynthesis, Transpiration, Water-Use Efficiency and Gene Expression of Two Sorghum bicolor (Moench) Genotypes Subjected to Dry-Down - Fracasso, Alessandra; Magnanini, Eugenio; Marocco, Adriano; Amaducci, Stefano (Frontiers in Plant Science, 2017)
Plant growth and productivity are strongly affected by limited water availability in drought prone environments. The current climate change scenario, characterized by long periods without precipitations followed by short but intense rainfall, forces plants to implement different strategies to cope with drought stress. Understanding how plants use water during periods of limited water availability is of primary importance to identify and select the best adapted genotypes to a certain environment. Two sorghum genotypes IS22330 and IS20351, previously characterized as drought tolerant and drought sensitive genotypes, were subjected to progressive drought stress through a dry-down experiment. A whole-canopy multi-chamber system was used to determine the in vivo water use efficiency. This system records whole-canopy net photosynthetic and transpiration rate of 12 chambers five times per hour allowing the calculation of whole-canopy instantaneous water use efficiency daily trends. Daily net photosynthesis and transpiration rates were coupled with gene expression dynamics of five drought related genes. Under drought stress, the tolerant genotype increased expression level for all the genes analysed, whilst the opposite trend was highlighted by the drought sensitive genotype. Correlation between gene expression dynamics and gas exchange measurements allowed to identify three genes as valuable candidate to assess drought tolerance in sorghum.